Moderating Religion for Global Security: Constructivist Insights - Ernada, Sus Eko Zuhri (The Indonesian Islamic Studies and International Relations Association (Insiera), 2025)
Religious moderation is important in state behaviour and international relations in the globalized world, impacting peace promotion and global security. The moderation of religion greatly inﬂuences the determination of state identity, adherence to international norms, and enhancement of diplomatic relations through promoting peaceful coexistence. This paper deliberates on the role of religious moderation using case studies of Indonesia, Norway, and India, referencing constructivist theory. The two most prominent Islamic organizations in Indonesia, Nahdlatul Ulama and Muhammadiyah, actively cooperate in reducing sectarian strife and enhancing pluralism, which beneﬁts both internal peace and the nation's improved international standing. Conversely, despite being a non-religious nation, Norway employs religious moderation as a strategic form of soft power, evidenced by its mediation eﬀorts in the Oslo Accords. This reinforces Norway's reputation as an impartial mediator in international crises. Meanwhile, India faces a rise in religious nationalism, mainly Hindu nationalism, which has worsened social polarization and made it more challenging to enact moderation in both foreign and domestic policy. Analyzing these cases highlights the challenges of religious extremism and nationalism while emphasizing the potential of religious moderation to support domestic stability, facilitate diplomacy, and contribute meaningfully to more considerable peacebuilding eﬀorts. Ultimately, this research underscores the critical importance of states incorporating moderate religious principles to promote internal harmony and contribute positively to international diplomacy and peace initiatives.